The earthquake in L'Aquila and the features of the three-dimensional P-velocity structure of the mantle beneath the Adriatic plate and its environment - V. I. Starostenko; A. V. Kendzera; I. V. Bugaenko; T. A. Tsvetkova (Геофизический журнал, 2011)
Confinement of the surface (crustal) earthquake happened on April 25 2009 in the area of the city Aquila in Italy to deep mantle processes under this area has been shown, which have been analyzed on the basis of three-dimensional P-velocity model of the mantle up to the depth of 2,500 km. This earthquake is confined to the area, which is characterized by certain sub-vertical dividing zone in the mantle where alternation (along the lateral) of the areas with high and low velocities takes place throughout all the depths